SPMA-NETS: SECURITY PROTOCOL BASED MOBILE AGENT IN MANETS - MAQBOL, AHMED; KAZAR, OKBA (Courrier du Savoir; Vol 22 (2017): COURRIER DU SAVOIR (JANVIER), 2017)
The security in the communication process is an important issue since the days of homing pigeons, where the people accustomed to send encrypted messages. In nowadays, with the technologies development, this issue is considered as a research field, which take a great part of attention. The mobile ad hoc network is aspect of the evolution of communication technology; it is defined a collection of mobile nodes, with no fixed infrastructure, resource constraints, communicate with each other using the radio medium, and dynamic creation and organization. The security issue is becoming a main concern in the applications of mobile ad hoc network. In this paper, we propose a security protocol for a mobile ad hoc networks based mobile agent, where the network is consisting of a set of nodes, each node has node agent for resources estimation of the node and communicate with others agents. The network is divided into a set of clusters; each cluster has to elect a node to be the head cluster, where the monitor agent will be reside. This monitor agent controls the communication inside cluster by collecting and analysing the data from the others nodes, it creates an inspector agent, which can move from one node to another to act like a local IDS in the visited node.